ANALISIS SEKTOR UNGGULAN PEREKONOMIAN DI KABUPATEN BOGOR - Rima Prasetya, Eka (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
This study aims to analyze the leading economic sectors towards economic growth in Bogor Regency. The method used is Location Quotient (LQ) and Shift Share (SS) analysis. The results showed that the water supply sector in Bogor Regency was the leading sector with a LQ value of 1,438, followed by 3 other sectors and there were 13 sectors that were not the leading sectors with LQ values below the average 1. Based on the results of Shift Share (SS) shows the manufacturing industry sector in Bogor Regency is in the top position and grows faster than the average provincial growth of 14,185,859.37, whereas if seen from its development, the information and communication sector is the most developed compared to other sectors However, when viewed from the competition in the regional share, the Wholesale and Retail Trade sector, Car and Motorcycle Repair has very strong competitiveness in the province of West Java